Sustainable investment decisions by medium sized power producers - Barth, Volker; Siebenhüner, Bernd (Ökologisches Wirtschaften - Fachzeitschrift, 2010)
Municipal utilities are an essential constituent of the German power sector and currently strongly expanding their generation capacities. Multiple factors influence these investment decisions. Are these investments more sustainable than those of other power producers, and what could be done to make them greener?
Keywords: Municipal utilities; power sector; investment decisions